Karakterisasi Fisika-Kimia Sabun Cuci Piring Berbasis Ekstrak Buah Mangrove Pedada (Sonneratia caseolaris) Sebagai Material Pembersih Ramah Lingkungan - Putri Kartiwi; Jumingin Jumingin; Atina Atina (Universitas PGRI Palembang, 2026)
The use of natural ingredients as components in eco-friendly cleaning products is an important alternative for reducing the impact of synthetic surfactants on human health and aquatic environments. This study aims to analyze the effect of adding pedada mangrove fruit extract (Sonneratia caseolaris) on the physicochemical characteristics of dishwashing soap as an eco-friendly cleaning agent. Extraction was performed using the maceration method with 96% ethanol, and the extract was formulated into liquid dish soap at varying concentrations of 0%, 10%, 15%, and 20%. The testing included phytochemical screening, viscosity, pH, homogeneity, organoleptic evaluation, and foam stability. The results of the phytochemical screening indicated the presence of flavonoids, tannins, and saponins, which have potential as natural antimicrobial agents. The addition of the extract caused a decrease in viscosity from 3550.21 cP to 932.95 cP as the extract concentration increased; however, all formulations still met the SNI 4075-2:2017 standard. The pH ranged from 6.06 to 6.44, which is considered safe for household use and relatively compatible with the skin’s physiological balance. Foam stability increased from 81.82% to 92.59% due to the presence of saponins, which act as natural surfactants. All formulations exhibited good homogeneity without phase separation. The formulation with a 15% extract concentration produced the most optimal and stable physical characteristics. This study indicates that pedada fruit extract has the potential to be developed as a coastal bio-based cleaning biomaterial that supports the concepts of green technology, environmental health, and the sustainability of aquatic ecosystems.